5-year comparison of selected balance parameters in artistic and rhythmic gymnastics - Leskovec, T.; Samardzija Pavletic, M. (International Scientific Congress Slovenian Gymnastics Federation, 2019)
Introduction: In sport and rhythmic gymnastics, the ability to maintain balance is very important. In rhythmic gymnastics they have to maintain the balance on reduce support surface »releve« and at the same time performing the movements of great amplitudes with other leg and also preforming manipulation with apparatus. In artistic gymnastics, maintaining the balance is important in dismounting the apparatus and landings. Therefore, we wanted to set normative values for selected balance parameters in the Slovenian gymnastic population. Methods: In the sample where included athletes from men`s artistic gymnastic (MAG), women`s artistic gymnastics (WAG) and rhythmic gymnastics (RG). It consisted from younger categories (from 8 to 13 years of age), junior category (from 14 to 15 years of age) and senior category (athletes who are 16 years old and older). The sample covered 926 measurements from a year 2014 to 2018. As a balance test we used single leg stance, with other leg bend at 90° in knee joint, with hands placed on their hips and open eyes. The following variables were selected for further analysis: total path of the centre of pressure (CoP) trajectory and path of the CoP in anterior-posterior and medial-lateral directions. Based on the obtained average values of the path of CoP we set the normative values for men`s and women`s artistic gymnastics and rhythmic gymnastics. Results: We found that there is a statistically significant difference between the WAG and RG group, while there is no statistically significant difference between MAG and WAG, MAG and RG. Also within disciplines between the categories are statistically significant differences, only in WAG group between junior and senior category there is no statistically significant difference. Regarding the normative values, the younger categories in all disciplines have the highest values, followed by the junior category and then the senior category. Discussion: We found that one-legged stance test with open eyes is a suitable test for setting the normative values for the selected population - competitors in artistic and rhythmic gymnastics. When determining normative values, it is necessary to separate sports disciplines between each other and also within the categories, only in WAG we can combine junior and senior categories.